Testosterone levels influence spatial ability: Further evidence for curvilinear relationship - Hromatko, Ivana (Array, 2006)
The aim of this study was to explore the influence of different testosterone levels on spatial ability. Four tests measuring various aspects of spatial ability were used. In the first part of the study tests were administered in three groups of subjects: two groups of healthy male volunteers - one tested in autumn (high-testosterone season) and the other one in spring (low-testosterone season), and a comparable group of females. In the second part of the study, a sub-sample of men was retested during a different season. The order of testing was counterbalanced. Spatial ability scores were compared both inter-individually (among groups with different presumed testosterone levels) and intra-individually (within subjects in different seasons). Between-subjects analyses showed that males in low testosterone season have higher spatial ability scores than both females and males in high testosterone season. In the within-subjects part of the study, repeated measures ANOVA showed no significant main effect of testosterone, but the interaction testosterone level x order of testing was significant: there was a greater rise in males' spatial ability scores if the second trial occurred during low testosterone season. Results are consistent with the hypothesis proposing curvilinear relationship between testosterone levels and spatial ability.